Phosphorylation of the nuclear poly(A) binding protein (PABPN1) during mitosis protects mRNA from hyperadenylation and maintains transcriptome dynamics - Gordon, Jackson M; Phizicky, David V; Schärfen, Leonard; Brown, Courtney L; Arias Escayola, Dahyana; Kanyo, Jean; Lam, TuKiet T; Simon, Matthew D; Neugebauer, Karla M (Nucleic acids research, 2024)
Polyadenylation controls mRNA biogenesis, nucleo-cytoplasmic export, translation and decay. These processes are interdependent and coordinately regulated by poly(A)-binding proteins (PABPs), yet how PABPs are themselves regulated is not fully understood. Here, we report the discovery that human nuclear PABPN1 is phosphorylated by mitotic kinases at four specific sites during mitosis, a time when nucleoplasm and cytoplasm mix. To understand the functional consequences of phosphorylation, we generated a panel of stable cell lines inducibly over-expressing PABPN1 with point mutations at these sites. Phospho-inhibitory mutations decreased cell proliferation, highlighting the importance of PABPN1 phosphorylation in cycling cells. Dynamic regulation of poly(A) tail length and RNA stability have emerged as important modes of gene regulation. We therefore employed long-read sequencing to determine how PABPN1 phospho-site mutants affected poly(A) tails lengths and TimeLapse-seq to monitor mRNA synthesis and decay. Widespread poly(A) tail lengthening was observed for phospho-inhibitory PABPN1 mutants. In contrast, expression of phospho-mimetic PABPN1 resulted in shorter poly(A) tails with increased non-A nucleotides, in addition to increased transcription and reduced stability of a distinct cohort of mRNAs. Taken together, PABPN1 phosphorylation remodels poly(A) tails and increases mRNA turnover, supporting the model that enhanced transcriptome dynamics reset gene expression programs across the cell cycle. Graphical Abstract Graphical Abstract